TOXIC FRIENDSHIP: UNDERSTANDING ADOLESCENT FRIENDSHIP - Imal Amalia (Universitas Pendidikan Indonesia, 2024)
Friendship plays an important role in adolescents' social, emotional development and mental well-being. This study aims to explore the role of friendship and the impact of toxic friendship on adolescent well-being. Descriptive qualitative research method was used to explore the phenomenon of adolescent friendship and its impact through literature study. The results showed that quality friendships, characterized by social support, familiarity, and mutual support, play a role in increasing adolescents' happiness and mental well-being. On the other hand, toxic friendships can cause various negative impacts, including stress, depression, and decreased self-esteem. Efforts are needed to build social skills, strengthen family relationships, and develop appropriate interventions to address toxic friendships.